2014
DOI: 10.1080/00380768.2014.929025
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient accumulation in aboveground biomass of planted tropical trees: a meta-analysis

Abstract: Efficient nutrient use is essential for biomass production by tropical trees growing in infertile soils. Accumulation of nitrogen (N) and phosphorus (P) in the aboveground biomass of four groups of tree stands [Acacia, Eucalyptus, N 2-fixing trees excluding Acacia, and other non-N 2-fixing broadleaved (ONNFB) trees] were investigated using meta-analyses of a range of biomass data to test the hypothesis that fast-growing Acacia and Eucalyptus trees accumulate fewer nutrients. Data for 83 tropical tree stands we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…This is in line with its foliar δ 15 N values, as N retention can lead to an enrichment in foliar δ 15 N (Unkovich ) and depleted A. longifolia foliar δ 15 N values compared to S. spectabilis were previously reported (Hellmann et al ). Depletion of foliar δ 15 N values could furthermore indicate P deficiency (Lazali et al ), however, symbiotic nitrogen fixation is barely affected by insufficient P (Augusto et al ), and the work presented here indicates that A. longifolia, like other Acacia species (Inagaki and Tange ), might show a high P use efficiency compared to other N 2 fixing legumes.…”
Section: Discussionmentioning
confidence: 64%
“…This is in line with its foliar δ 15 N values, as N retention can lead to an enrichment in foliar δ 15 N (Unkovich ) and depleted A. longifolia foliar δ 15 N values compared to S. spectabilis were previously reported (Hellmann et al ). Depletion of foliar δ 15 N values could furthermore indicate P deficiency (Lazali et al ), however, symbiotic nitrogen fixation is barely affected by insufficient P (Augusto et al ), and the work presented here indicates that A. longifolia, like other Acacia species (Inagaki and Tange ), might show a high P use efficiency compared to other N 2 fixing legumes.…”
Section: Discussionmentioning
confidence: 64%
“…The influence of nutrient bioavailability on accumulation in the trees was weak for N, while the amounts of P, K, Ca and Mg accumulated in the trees at the end of the cycle reflected their bioavailability, either as exchangeable elements in the soil, or added as fertilizer. A meta-analysis for tropical tree species in planted forests highlighted a similar pattern, with phosphorus use efficiency to produce biomass that was much more variable than nitrogen use efficiency (Inagaki and Tange, 2014) (Fig. 7).…”
Section: Influence Of the Fertilization Regime And Soil Conditions Onmentioning
confidence: 77%
“…Fast-growing tree species are generally considered to accumulate soil nutrients faster than slow-growing ones when multiple rotations are implemented (Cossalter and Pye-Smith 2003). Inagaki and Tange (2014) also reported that fast-growing Eucalyptus trees can accumulate more aboveground biomass than N2-fixing and other non-N2-fixing broadleaved trees while incorporating less aboveground N. Furthermore, some Acacia and Eucalyptus trees can produce more aboveground biomass than other non-N2-fixing broadleaved trees while using less P. Montagnini (1998) reported that four years after planting, decrease in soil nutrients were apparent in pure plots of some of the fastest growing species. On the other hand, Some fast-growing tree species have strategies that allow them to grow on degraded soils.…”
Section: Discussionmentioning
confidence: 96%